Characteristic Slow‐Slip Events on the Superstition Hills Fault, Southern California - Ellis J. Vavra; Yuri Fialko; Thomas Rockwell; Roger Bilham; Petra Štěpančíková; Jakub Stemberk; Petr Tábořík; Josef Stemberk (Geophysical Research Letters)
Abstract The Superstition Hills Fault (SHF) exhibits a rich spectrum of slip modes, including M 6+ earthquakes, afterslip, quasi‐steady creep, and both triggered and spontaneous slow slip events (SSEs). Following 13 years of quiescence, creepmeters recorded 25 mm of slip during 16–19 May 2023. Additional sub‐events brought the total slip to 41 mm. The event nucleated on the northern SHF in early‐May and propagated bi‐laterally at rates on the order of kilometers per day. Surface offsets reveal a bi‐modal slip distribution, with slip on the northern section of the fault being less localized and lower amplitude compared to the southern section. Kinematic slip models confirm systematic variations in the slip distribution along‐strike and with depth and suggest that slip is largely confined to the shallow sedimentary layer. Observations and models of the 2023 SSE bear a strong similarity to previous slip episodes in 1999, 2006, and 2010, suggesting a characteristic behavior.